(3GdeMGSHI GdeGdjI GdeJhSWIs - (3QVhGf eMeO(B, (3GdYfGJjs ((3YeGf(B:s (3OGQ JSfje ddfTQ hGdJhRjY(B,s, 2006)
(3GdCNWGA GdeMGSHjI heYGdLJgG, LQO GdMSGHGJ GdhgejI, LQO GdCUhd GdeJOGhdI, LQO GdCUhd GdKGHJI, GdEdJRGeGJ bUjQI GdCLd, bGFeI GdJOabGJ GdfbOjI, GdEYJQGa HGdEjQGOGJ, CKQ GdJShjGJ GdLQOjI Ydi GdbhGFe GdeGdjI, GdbjeI GdRefjI ddfbhOs
(3HHdjhZQGajG(B: (3U(B.269(3; edGMb U(B.259 s
Keywords: (3GdeMGSHI (B-(3GdeGdjI GdYGeIs